EFEKTIVITAS LAYANAN KONSELING KELOMPOK PADA MAHASISWA DI SEKOLAH TINGGI DIAKONES HKBP BALIGE - Lamria Sinaga (Universitas Nias Raya, 2026)
This study aims to examine the effectiveness of group counseling services in a theological higher education institution. It employs a descriptive qualitative research method through Focus Group Discussions (FGD) conducted with ten theology students who participated in group counseling services at the institution. The findings reveal that STD HKBP, as a theological higher education institution, organizes group counseling services for students in various forms, such as academic guidance groups, art groups, creativity groups, dormitory fellowship groups, and class-based groups. Group counseling provides benefits by helping its members grow and develop according to the type of group counseling they participate in. In addition, group counseling contributes to the development of students’ competencies and skills.